Psychological distress among orphaned youth and youth reporting sexual exploitation in Kampala, Uganda. (December 2020) - Perry, Elizabeth W.; Culbreth, Rachel; Swahn, Monica; Kasirye, Rogers; Self-Brown, Shannon
Highlights: Psychological distress is common among street and slum youth in Kampala. Psychological distress is high among Ugandan orphans and sexually exploited youth. Double orphanhood is associated with reporting worry and hopelessness. Sexual exploitation is associated with reporting worry and hopelessness. Abstract: Psychological distress is a priority health issue in low- and middle-income countries; however, it is inadequately addressed among vulnerable youth living in extremely underserved communities (i.e., on the streets and in the slums) who are at a high risk of experiencing adversity. The purpose of this study was to compute the prevalence of self-reported psychological distress among youth living in the slums and on the streets of Kampala, Uganda, and examine how orphan status and commercial sexual exploitation (CSE) are related to youth psychological distress. Analyses are based on a 2014 cross-sectional survey of service-seeking youth ( N  = 1134) in Kampala, Uganda. Bivariate and multivariable multinomial regression analyses were used to determine associations between orphan status, sexual exploitation, and psychological distress (defined as experiencing the following proxy variables for more complex psychopathology: hopelessness and/or worry). Among all youth participants, 83.2% ( n  = 937) reported at least one type of psychological distress; 51.3% ( n  = 578) reported experiencing both types. The reported prevalence of any type of psychological distress was highest among youth who reported experiencing sexual exploitation (91.2%), double orphans (90.0%), and single orphans (83.8%); however, a high prevalence (76.7%) of any type of distress was also found among youth who reported both parents alive. Experiencing both types of distress was associated with being a double orphan (adjusted odds ratio [AOR] = 2.92, 95% confidence interval [CI] = [1.77, 4.81]), reporting CSE (AOR = 2.71, 95% CI = [1.67, 4.41]), and increased age (AOR = 1.31, 95% CI = [1.20, 1.44]). Psychological distress is prevalent among all youth living in the slums of Kampala and is independently associated with being a double orphan and experiencing CSE. These findings underscore the urgent need to intervene with all youth who reside in this particular underserved community, especially those who have lost both parents, and to prevent CSE among this vulnerable, underserved population.